A violência contra a mulher: um estudo comparativo sobre a atuação da rede de proteção social no município de Miracema do Tocantins - Lira Sobrinho, Mária (Universidade Federal do Tocantins, 2023)
This monograph is the result of a study carried out in the municipality of Miracema do Tocantins, near the women's care network, with the main objective of identifying the care provided to women victims of domestic violence in that city. In addition, we conducted a comparative study of the changes in the Policy to Protect Women Victims of Violence in Miracema-TO in the last two years (2017/2019), from a comparative analysis. In order to collect the data, the qualitative approach was applied through the semi-structured interview technique, observing the weaknesses of the women's protection network. According to the data collected through the field research, it is concluded through critical approaches that the Miracema do Tocantins women's care network goes through countless factors, which hinder the confrontation of violence in the city, since the Police Station of Women Service is the only body specialized in care of the city, however, does not offer any specialization to professionals to care for women, not to mention the fact of the weakness of the lack of a Social Work professional in the body. Thus, due to the presented, there is a shortage of professional qualification and failures in women's protection services, considering that the confrontation of violence is daily and needs qualified services to combat violence against women. Especially at a time when conservatism and the persecution of gender issues are increasing in the light of human rights.